Influence of Polymer Aggregation and Liquid Immiscibility on Morphology Tuning by Varying Composition in PffBT4T‐2DT/Nonfullerene Organic Solar Cells. Issue 8 (29th January 2020) - Hamid, Zeinab; Wadsworth, Andrew; Rezasoltani, Elham; Holliday, Sarah; Azzouzi, Mohammed; Neophytou, Marios; Guilbert, Anne A. Y.; Dong, Yifan; Little, Mark S.; Mukherjee, Subhrangsu; Herzing, Andrew A.; Bristow, Helen; et al.
Abstract: The temperature‐dependent aggregation behavior of PffBT4T polymers used in organic solar cells plays a critical role in the formation of a favorable morphology in fullerene‐based devices. However, there is little investigation into the impact of donor/acceptor ratio on morphology tuning, especially for nonfullerene acceptors (NFAs). Herein, the influence of composition on morphology is reported for blends of PffBT4T‐2DT with two NFAs, O‐IDTBR and O‐IDFBR. The monotectic phase behavior inferred from differential scanning calorimetry provides qualitative insight into the interplay between solid–liquid and liquid–liquid demixing. Transient absorption spectroscopy suggests that geminate recombination dominates charge decay and that the decay rate is insensitive to composition, corroborated by negligible changes in open‐circuit voltage. Exciton lifetimes are also insensitive to composition, which is attributed to the signal being dominated by acceptor excitons which are formed and decay in domains of similar size and purity irrespective of composition. A hierarchical morphology is observed, where the composition dependence of size scales and scattering intensity from resonant soft X‐ray scattering (R‐SoXS) is dominated by variations in volume fractions of polymer/polymer‐rich domains. Results suggest an optimal morphology where polymer crystallite size and connectivity are balanced, ensuring a high probability of hole extraction via such domains. Abstract : The dependence of performance on composition in organic solar cells based on PffBT4T‐2DT polymer with O‐IDTBR or O‐IDFBR as a nonfullerene acceptor is investigated. The effect on morphology is discussed in terms of the interplay between immiscibility, inferred from phase behavior, and polymer aggregation. Morphology is optimized when polymer crystallite interconnectivity and size are balanced.